2016
DOI: 10.1111/azo.12182
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasurface structure of oromandibular area in a hill stream teleost Glyptothorax trilineatus Blyth, 1860

Abstract: Kaushik, G. and Bordoloi, S. 2017. Ultrasurface structure of oromandibular area in a hill stream teleost Glyptothorax trilineatus Blyth, 1860. -Acta Zoologica (Stockholm) 98: 362-369.Ultrasurface structure of the oromandibular area of a hillstream catfish Glyptothorax trilineatus Blyth 1860, an inhabitant of the sub-Himalayan streams of India is described. Scanning electron microscopic (SEM) study of these areas revealed a series of punctuation elevation from the general surface epithelium. Two types (types I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Benthic and nocturnal fishes and fishes from turbid waters are equipped with plentiful external TBs, whereas in pelagic fishes and fishes from transparent waters density is usually considerably lower (Davis & Miller, 1967;Gomahr et al, 1992). Generally, external TBs are most heavily concentrated on the parts of body surfaces with the highest probability of contact with a food item during fish foraging, such as the lips, barbels and pectoral fins, with TBs gradual decreasing in abundance posteriorly (Atema, 1971;Fox, 1999;Gomahr et al, 1992;Harvey & Batty, 2002;Kaushik & Bordoloi, 2016;Zhang et al, 2006 (Scharrer et al, 1947;Harvey & Batty, 2002).…”
Section: The Anatomy and Physiology Of The Taste System In Fishesmentioning
confidence: 99%
“…Benthic and nocturnal fishes and fishes from turbid waters are equipped with plentiful external TBs, whereas in pelagic fishes and fishes from transparent waters density is usually considerably lower (Davis & Miller, 1967;Gomahr et al, 1992). Generally, external TBs are most heavily concentrated on the parts of body surfaces with the highest probability of contact with a food item during fish foraging, such as the lips, barbels and pectoral fins, with TBs gradual decreasing in abundance posteriorly (Atema, 1971;Fox, 1999;Gomahr et al, 1992;Harvey & Batty, 2002;Kaushik & Bordoloi, 2016;Zhang et al, 2006 (Scharrer et al, 1947;Harvey & Batty, 2002).…”
Section: The Anatomy and Physiology Of The Taste System In Fishesmentioning
confidence: 99%
“…The importance of breathing valves has been shown in several studies (Alsafy et al, 2022;El Bakary, 2012;Elgendy et al, 2016;Kaushik & Bordoloi, 2017;Nandi & Saikia, 2021). The breathing valve (velum) is crucial in preventing water reflux and food escape (Dahlgren, 1898;Hughes & Hughes, 1963).…”
Section: Discussionmentioning
confidence: 98%
“…While Bemis et al (2019) concentrated on tooth development and replacement, the present research elucidated anatomical and morphological aspects of the entire oropharyngeal cavity. The morphology and arrangement of these fangs may play essential roles in capturing, retaining and eating food these types of teeth are generally found in carnivorous (predatory) fish (Kaushik & Bordoloi, 2017). It was indicated that in Oxycheilinus digramma the fangs were primarily to capture prey ensuring puncturing of prey skin, whereas the short conical teeth for gripping and cutting prey after capture, whereas others mentioned that the jaws and pharyngeal teeth in some fish species assisted with mastication and crushing of the food prior to swallowing (Mihalitsis & Bellwood, 2019; Sibbing, 1982; Vandewalle et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Although the light cells are believed to be associated with gustatory chemoreception, the dark cells are thought to mainly involve in providing greatly increased surface area for secretion of material into the taste bud pore (Ovalle & Shinn, 1977). The distribution pattern in taste buds reflects fishes’ feeding habits, strategies, and habitats (Kiyohara et al, 1980; Gomahr et al, 1992; Fishelson & Delarea, 2004) and also is indicative of possible mechanisms of foraging and food recognition (Fishelson et al, 2004). In the present study, we visualized the presence of both shorter and longer microvilli comprising of the dark and light cells, respectively, in the rostral and maxillary barbels of the four fish.…”
Section: Discussionmentioning
confidence: 99%